Metastasis of Ewing's sarcoma to the thyroid gland: A case report. (October 2018) - Appachi, Swathi; Meleca, Joseph B.; Krakovitz, Paul
Abstract: Ewing's sarcoma (ES) is an aggressive pediatric malignancy. We present a case of ES with thyroid metastasis. The patient was diagnosed with ES at age 8. Despite aggressive treatment, she suffered disease progression. Surveillance demonstrated a left thyroid lesion. This grew rapidly within 2 months, causing tracheal compression. She underwent hemi-thyroidectomy to prevent airway compromise. Due to her refractory ES, she was enrolled in the Vigil immunotherapy vaccine trial; thus, the specimen was used for vaccine development. This is the first reported case of skeletal ES with metastasis to the thyroid, requiring hemithyroidectomy to prevent airway compromise.